INSTALASI PERANGKAT PRODUKSI PADA PROSES PENGERINGAN BIJI BUNGA MATAHARI DI KELOMPOK TANI DESA CIHANJUANG BARAT - Nunung Nurhasanah; Muthohar, Akhmad (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2023)
Sunflower (Helianthus annuus L.) is a perennial plant originating from Mexico and Peru. This plant has high value-added when processed into cooking oil, herbal oil, and livestock feed. Global oil production is only able to meet a demand of 0.26%. Indonesia has the opportunity to develop the cultivation of this plant to enhance its added value and global competitiveness. Community empowerment activities aim to improve the welfare of sunflower farmers and raise social awareness among students regarding the surrounding community. Problems in the production sector are: (i) farmers cannot ensure that sunflower seeds that have been dried have a moisture content of 12%, (ii) the drying process in some places still relies on sunlight, and cannot anticipate if it rains. So, based on the analysis carried out, we carried out empowerment activities in the form of installing production installing production equipment in the sunflower seed drying process for farmer groups in the village of Cihanjuang Barat. Socialization and guidance on the use of equipment was carried out to farmers regarding production equipment that can help the production process. After the installation has been successfully carried out, the sunflower seeds reach a moisture content of 12% according to the wishes of the farmers and it is hoped that they can replace conventional sunflower seed drying processes such as which was done previously.